(untitled) (CAHIERS MAGELLANES-NS, 2024)
Environmental and animal welfare education are closely bound, bestowing an understanding of the sacred nature of life and a reverence for everything living, including animals. Environmental education fosters a culture of protecting the environment, adapting to the sustainable use of environmental resources, and realizing human being’s effects on the environment. At the same time, education on the rights of animals brings an appreciation of our stewardship towards the many species populating our world. Therefore, schools should adopt two angles to develop informed, empathetic, and responsible citizens of the country. The researcher has thoroughly searched environmental and animal welfare education, and the information used in this insightful article was obtained from this research. There is a brief analysis of what the two types of education mean and what they entail, underlining their significance. These can include knowledge of ecosystems, the promotion of sustainable living, and valuing the human effects on the environment. Furthermore, it also discusses the concept of animal welfare education that should primarily aim at cultivating such proactive values as mercy and ethically moral attitude toward animals. Writing for this study, the author claims that integrating such components in education circulation is imperative in nurturing an environmentally conscious generation that positively contributes to humanity and the planet.